2005
DOI: 10.1063/1.1925757
|View full text |Cite
|
Sign up to set email alerts
|

Large negative magnetoresistance in a ferromagnetic shape memory alloy: Ni2+xMn1−xGa

Abstract: 5% negative magnetoresistance (MR) at room temperature has been observed in bulk Ni2+xMn1−xGa. This indicates the possibility of using Ni2+xMn1−xGa as magnetic sensors. We have measured MR in the ferromagnetic state for different compositions (x=0–0.2) in the austenitic, premartensitic, and martensitic phases. MR is found to increase with x. While MR for x=0 varies almost linearly in the austenitic and premartensitic phases, in the martensitic phase it shows a cusplike shape. This has been explained by the cha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
97
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(109 citation statements)
references
References 23 publications
5
97
1
2
Order By: Relevance
“…This enhancement reflects Ni-d and Mn-d electronic contributions to the majority-spin density of states and is accompanied by significant reconstruction of the Fermi surface. Ni-Mn-Ga alloys with near-stoichiometric compositions, Ni 2 MnGa, are important functional materials [1] owing to their magnetic shape-memory [2], magnetocaloric [3] and magnetoresistive [4] properties. This ferromagnetic fcc L2 1 Heusler (a fcc = 5.81Å) was first identified by Webster et al [5] as a system undergoing a martensitic transition (MT) in its ferromagnetic phase (T C ∼ 380 K) with little magnetic hysteresis.…”
mentioning
confidence: 99%
“…This enhancement reflects Ni-d and Mn-d electronic contributions to the majority-spin density of states and is accompanied by significant reconstruction of the Fermi surface. Ni-Mn-Ga alloys with near-stoichiometric compositions, Ni 2 MnGa, are important functional materials [1] owing to their magnetic shape-memory [2], magnetocaloric [3] and magnetoresistive [4] properties. This ferromagnetic fcc L2 1 Heusler (a fcc = 5.81Å) was first identified by Webster et al [5] as a system undergoing a martensitic transition (MT) in its ferromagnetic phase (T C ∼ 380 K) with little magnetic hysteresis.…”
mentioning
confidence: 99%
“…It is argued that the underlying mechanisms are mainly governed by the s-d scattering for the bulks and the spin transport for the thin films. 10,11 Among the Heusler alloys, Ni-Mn-Ga single crystals exhibit giant magnetic field-induced strains ͑MFISs͒ of ϳ6% ͑load-free͒ in the tetragonal martensitic phase and of ϳ10% in the orthorhombic martensitic phase as a result of the martensitic twin-variant reorientation induced by magnetic field, mechanical stress, and/or temperature. [13][14][15] This reorientation may also lead to a characteristic change in electrical resistivity due to crystallographic anisotropy.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 More recently, the MR effect has been observed in some half-metallic Heusler alloys with the general formula Ni 2 Mn 1+x X 1−x ͑where X is a sp-element such as Sn, Sb, In, etc.͒ and in some Heusler-type ferromagnetic shape memory alloys ͑such as Ni-Mn-Ga alloys͒. [7][8][9][10][11][12] In particular, the reported MR effect in these Heusler alloys is basically in polycrystalline bulks and thin films with either positive or negative MR value, depending on applied magnetic field and ͑low͒ temperature. It is argued that the underlying mechanisms are mainly governed by the s-d scattering for the bulks and the spin transport for the thin films.…”
Section: Introductionmentioning
confidence: 99%
“…This magnetically controlled resistivity/resistance ͓referenced as magnetoresistance ͑MR͒ effect͔ shows a potential application in novel magnetic memory storage device. 11 Current study on the MR effect of Ni-Mn-Ga alloy have been mostly carried out in polycrystalline system, [12][13][14] where MR effect can be understood by spin transport mechanism that considered different magnetization processes in large ferromagnetic clusters and spin reorientation of small clusters and boundary spins. However, the study on the electrical resistivity in different single-variant state is rarely reported in experimental observation and theoretical calculation.…”
Section: Introductionmentioning
confidence: 99%